Improving Monascus pigment in Monascus fermented durian seed using rice flour - Alvino, Jonathan; Nugerahani, Ira; Dharma, Arya Wira; Srianta, Ignatius (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Monascus fermented durian seed (MFDS) can be helpful as a natural dye that has the potential to anticancer, anti-hypercholesterolemia, anti-diabetic, and others. Pigment production in MFDS is still relatively low compared to complex starch media. This research aimed to improve the pigment production in MFDS by adding rice flour. The research design used was a Randomized Block Design with one factor, namely the concentration of rice flour consisting of six levels that are 0%, 2%, 4%, 6%, 8%, and 10%. The results showed that adding rice flour affected the color and levels of water-soluble pigment and ethanol in MFDS. The higher concentration of rice flour decreased the value of lightness and increased the value of redness, yellowness, and chroma, as well as improving the levels of water and ethanol-soluble pigment. Highest ethanol and water-soluble pigment produced in MFDS with 10% rice flour, which produced a yellow pigment content of 9.814 - 10.609 AU/g; orange pigment 3.065 - 8.074 AU/g; and red pigment 4.134 - 8.085 AU/g. The intensity of the MFDS pigments also increased with the higher concentration of rice flour added.